A novel flexible barrier for landslide impact in centrifuge. Issue 3 (4th August 2016) - Ng, C. W. W.; Song, D.; Choi, C. E.; Koo, R. C. H.; Kwan, J. S. H.
Abstract : Experimental investigations aimed at understanding the impact mechanism of debris-resisting flexible barriers have been hindered by limitations associated with small-scale modelling and poor temporal predictability of real landslide debris events. The geotechnical centrifuge provides a means to simulate landslide impact by scaling the flow volume, impact energy and stress state appropriately. Nonetheless, a technical challenge remains in simulating large non-linear deformation of flexible barriers observed in a prototype. In this letter, the development and verification of a novel model flexible barrier for centrifuge testing are described. This model barrier consists of a series of spring elements to simplify the complex loading behaviour and to capture the key bilinear load–displacement response of a prototype flexible barrier. By measuring the dynamic response of barrier cables, no obvious peak impact load was captured. The shear strength of dry granular flow results in an attenuating pileup impact mechanism. It is apparent that the geometry of the debris front has a strong influence on impact response. In addition, as debris impacts and deposits behind the barrier, the debris–barrier interaction results in an active failure mode of the deposited material, which is a surrogate of reduced pressure acting on the barrier.